Efficiency of Enterprise Management Based on Controlling in Central Asia (Texas Journal of Multidisciplinary Studies, 2025)
This article explores the effectiveness of controlling systems in improving enterprise management efficiency in Central Asia. By analysing the unique economic, cultural, and regulatory conditions in the region, this study demonstrates how controlling mechanisms contribute to better resource allocation, cost management, and decision-making. It also addresses challenges such as managerial expertise and access to technology, emphasizing the need for adaptable and scalable controlling systems. The findings suggest that enterprises in Central Asia can enhance their competitiveness by integrating controlling practices tailored to the region's specific conditions